2011
DOI: 10.1371/journal.pone.0024950
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Associated with Metastatic Prostate Cancer

Abstract: ObjectiveMetastasis is the most common cause of death of prostate cancer patients. Identification of specific metastasis biomarkers and novel therapeutic targets is considered essential for improved prognosis and management of the disease. MicroRNAs (miRNAs) form a class of non-coding small RNA molecules considered to be key regulators of gene expression. Their dysregulation has been shown to play a role in cancer onset, progression and metastasis, and miRNAs represent a promising new class of cancer biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
149
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(157 citation statements)
references
References 79 publications
(123 reference statements)
6
149
1
1
Order By: Relevance
“…Similar to the association we observed for miR339-5p, higher expression was associated with lower metastasis rates, and in addition reduced cancer cell growth and better patient survival in breast cancer (49). Also for prostate cancer, lower expression of miR339-5p was observed in metastatic cancer (50).…”
Section: Discussionsupporting
confidence: 84%
“…Similar to the association we observed for miR339-5p, higher expression was associated with lower metastasis rates, and in addition reduced cancer cell growth and better patient survival in breast cancer (49). Also for prostate cancer, lower expression of miR339-5p was observed in metastatic cancer (50).…”
Section: Discussionsupporting
confidence: 84%
“…Two recent studies reported increased serum levels of miR-375 (and miR-141) in patients with metastatic prostate carcinoma (26,27). In contrast, a miRNA profiling approach based on high-throughput sequencing by Watahiki and colleagues did not find an increase of miR-375 in metastatic prostate carcinoma (28). Other studies using microarray analysis also did not find an induction of miR-375 in prostate carcinoma (reviewed in refs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR-205 was shown to be downregulated in advanced-stage PCa in our studies (Figure 1a and 1b) and to be down-regulated in metastatic PCa. 23 Chung et al 24 reported that the aberrant expression of miR-205 took place in advanced stages in endometrial cancer. In addition, previous studies have shown that the level of miR-205 was inversely correlated with PSA and tumor stage.…”
Section: Mir-205 Suppresses Tumor Growth In Vivomentioning
confidence: 99%